(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The legitimacy of the authority in its exercise of its authority over the governed in democratic systems is linked through the election of these rulers with free and fair elections organized through an electoral system. effective representation in Parliament. In Iraq, which adopted the parliamentary system after 2005, the electoral systems were affected by a number of factors, by several electoral processes, which had a significant impact on the weakness and instability of the electoral system, as well as the diversity of the electoral system between the closed-list system, the "proportional representation system", and the development into The "open lists system", as a result of societal developments imposed by the stage, as the Iraqi legislator switched from the proportional representation system with the lists system to the system of individual nomination and medium-numbered constituencies, which we will address in the body of the research.